Analisis Faktor-Faktor yang Mempengaruhi Motivasi dan Pengaruhnya terhadap Peningkatan Kinerja Karyawan - Ardhyan Krisdiyanto (STIE Widya Manggala, 2010)
RS. Roemani Muhammadiyah Semarang has problems on its employee’s performances which most of them stay in enough classification, not in good classification. This research investigates the influence of training and development, Job satisfaction, Organizational culture, and motivation to improve employee performance.A research model was designed to reflect those important factors. Data was taken from employees of RS. Roemani Muhammadiyah Semarang. Population of this research was 700 people. This research used purposive sampling method and earned 140 respondents. Data was collected by using questionnaire and interview to respondents. The results indicate that training and development factor was positively influence employee performance, directly or through motivation. Job satisfaction factor was positively influence employee performance, directly or through motivation. Organizational culture factor was positively influence employee performance, directly or through motivation. Moreover, motivation positively and significantly influenced employee performance. Limitation and agenda for the further research can be used as reference by further researcher.